Periodontal condition in patients with rheumatoid arthritis - Ishi, Eduarod de Paula [UNESP]; Bertolo, Manoel Barros; Rossa Júnior, Carlos [UNESP]; Kirkwood, Keith Lough; Onafre, Mirian Aparecida [UNESP] (FapUNIFESP (SciELO), 2008)
The purpose of this clinical study was to investigate if periodontal disease and rheumatoid arthritis (RA) are associated. The study included 39 RA patients (test group) and 22 age- and gender-matched healthy individuals (control group). Questionnaires on general and oral health were applied and a complete periodontal exam, including visible plaque, marginal bleeding, attachment loss (AL) and number of teeth present, was also performed by a single calibrated examiner. Diabetes mellitus patients and smokers were excluded. RA patients had fewer teeth, higher prevalence of sites presenting dental plaque and a higher frequency of sites with advanced attachment loss. Although the prevalence of dental plaque was higher in the test group (Chi-square test, p = 0.0006), the percentage of sites showing gingival bleeding was not different (Fisher's exact test, p > 0.05). Based on our results, we suggest that there is an association between periodontal disease and RA.
Keywords: Periodontal attachment loss; Periodontitis; Rheumatoid arthritis; adult; age distribution; case control study; cross-sectional study; female; health; human; male; middle aged; mouth hygiene; periodontal disease; periodontitis; rheumatoid arthritis; sex ratio; Adult; Age Distribution; Arthritis, Rheumatoid; Case-Control Studies; Cross-Sectional Studies; Female; Humans; Male; Middle Aged; Oral Health; Oral Hygiene; Periodontal Attachment Loss; Periodontal Diseases; Sex Distribution